2015
DOI: 10.1007/s40011-015-0667-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Isoproturon by Bacillus pumilus K1 Isolated from Foothill Agroecosystem of North West Himalaya

Abstract: Isoproturon (IPU) degrading bacterium was isolated from herbicide treated soils. Morphological, biochemical and 16S rRNA sequencing revealed that the strain belonged to the phylogeny of the Bacillus sp. (99 % sequence similarity with Bacillus pumilus FM 201790.1) hence designated as B. pumilus K1. Biodegradation study was carried out using 200 mg L -1 IPU as sole source of carbon at three pH levels i.e. 6.5, 7.0 and 7.5 and three temperatures i.e. 25, 30 and 35°C. In the first 5-10 days IPU biodegradation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The expressed E. coli showed a high biodegradation efficiency compared with the P. putida wild-type. Biodegradation efficiency was determined using HPLC by determining the remaining IPU after the incubation period, it was observed that at first five days, the efficiency of expressed E. coli degradation was slow in comparison to P. putida , which could demonstrate the lag phase while it got accelerated as the incubation performed, most probable due to enzymes activation in the inoculated cultures (Giri et al 2017 ). In this study, gene expression analysis of cloned catA was compared to catA expression from P. putida using qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expressed E. coli showed a high biodegradation efficiency compared with the P. putida wild-type. Biodegradation efficiency was determined using HPLC by determining the remaining IPU after the incubation period, it was observed that at first five days, the efficiency of expressed E. coli degradation was slow in comparison to P. putida , which could demonstrate the lag phase while it got accelerated as the incubation performed, most probable due to enzymes activation in the inoculated cultures (Giri et al 2017 ). In this study, gene expression analysis of cloned catA was compared to catA expression from P. putida using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC analysis was carried out at room temperature. Residual IPU concentration was quantified utilizing a standard curve plotted between the IPU knew concentration and mass absorbance unit (mAU) (Giri et al 2017 ). All the HPLC solvents (the dichloromethane cat.…”
Section: Methodsmentioning
confidence: 99%
“…Residual IPU and its metabolites were extracted and processed using the previously described methodology (Giri et al 2015 ). The IPU extracts were then analyzed using Dionex HPLC equipped with auto sampler and Acclaim 120, C 18 5 µm 4.6 × 250 mm column.…”
Section: Methodsmentioning
confidence: 99%
“…Biostimulation involves the addition of adequate nutrients in the medium to enhance pesticide degradation potential of native microbes (Couto et al 2010 ) or to promote cometabolism (De Lorenzo 2008 ). Biostimulation is one of the major strategies, which has been implemented for the bioremediation of a wide variety of xenobiotics (Kadian et al 2008 ; Giri et al 2015 ). Although the microbial communities existing in contaminated sites harbour the pesticide catabolising genes and enzymes, lack of electron acceptors or donors, nutrient availability or delayed stimulation of the metabolic pathways essential for degradation acts as limiting factors for pesticide degradation.…”
Section: Introductionmentioning
confidence: 99%